THE HOTEL DEPARTMENT STANDARDIZATION TO IMPROVE STUDENT COMPETENCE IN THE HOUSEKEEPING AND FRONT OFFICE DEPARTMENT THROUGH FIELD INDUSTRIAL PRACTICES IN MATARAM CITY AND WEST LOMBOK - Firman Koma Febdilan (Bajang Institute, 2022)
PKL is the term for Field Practice or Professional Placement program. PKL is one systematic implementation within educational programs with mastering skills obtained by undergoing work placement in the working world. The program itself is actually beneficial for students and enterprises. The skills obtained on the campus can be applied in PKL. Hence, it can determine how well students can apply the knowledge and skills derived through the PKL program to become evaluations to develop education quality. The purpose of conducting this research is to determine how the industry's strategy and the steps taken to develop or enhance the skills of the training students in Housekeeping and Front Office, particularly in performing the duties conforming to the predetermined set of the standard by the respective industries. The data collection technique used is observation, interview, literature study, and documentation, which was analyzed using the interactive communication data analysis model by reducing the data, conducting data presentation, and drawing the conclusion. This research results show that the hotelier had applied basic comprehension that the students must know, such as hotel area, hotel property, and the profile of all hotel departments. Additionally, they all implement program standardization after understanding basic product knowledge and dividing work sections in the Housekeeping and Front Office. In Housekeeping, the working standardizations applied are General knowledge of front office, Front Desk Agent, Service center, Bellboy, Guest relation officer. While housekeeping had implemented standardizations such as general training knowledge of housekeeping, room, and laundry.